2022
DOI: 10.1016/j.jmig.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcomes after Laparoscopic Myomectomy: Conventional versus Barbed Suture

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Other studies have also reported similar reductions in abortion rates post-myomectomy, ranging from 41-60% to 19-24% [27,28]. However, even with these improvements, the abortion rate post-myomectomy remains higher than in the general population (10-15%) [11]. The incidence of ectopic pregnancies after myomectomy was slightly higher (4%) than in the general population.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Other studies have also reported similar reductions in abortion rates post-myomectomy, ranging from 41-60% to 19-24% [27,28]. However, even with these improvements, the abortion rate post-myomectomy remains higher than in the general population (10-15%) [11]. The incidence of ectopic pregnancies after myomectomy was slightly higher (4%) than in the general population.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, Alessandro Arena's [14] investigation into barbed and non-barbed techniques demonstrates no uterine ruptures among 83 and 81 participants, respectively, indicating a possible lower risk associated with these methods. Furthermore, Paul P. G.'s [11] study corroborates these findings, reporting no uterine ruptures in cohorts employing both barbed and non-barbed techniques. This synthesis of evidence underscores the significance of suture selection in mitigating the risk of uterine rupture during fertility-related procedures, with potential implications for clinical decision-making in reproductive health interventions.…”
Section: Intraoperative Techniques (Type Of Suture) and Uterine Rupturementioning
confidence: 62%
See 2 more Smart Citations
“…A study by Bures et al 7 compared the complication rates between barbed and traditional sutures in bariatric anastomosis procedures and found no significant difference. Similarly, a retrospective cohort study by Paul et al 8 found that barbed sutures posed no statistically significant risk for complication after laparoscopic myomectomy when compared with conventional sutures. In addition, the literature suggests that barbed sutures offer advantages in obstetric procedures that standard sutures do not 9 .…”
Section: Discussionmentioning
confidence: 91%